Statistical waves of the budgetary financing of education and science in Ukraine - Totska, Olesia Leontiivna; Тоцька, Олеся Леонтіївна (The Annals of the Stefan cel Mare University of Suceava, Fascicle of the Faculty of Economics and Public Administration, 2011)
In the article an author analysed the indexes of profits, charges and deficit of the State budget of Ukraine for 2002–2011. The prognosis model of the budgetary financing of Ukrainian education and science is built. The dynamics of particles of the government spending on education and science in profits and charges of country is determined. The name of statistical waves of the budgetary financing of education and science in Ukraine is given to these indexes. У статті автором проаналізовано показники доходів, видатків і дефіциту Державного бюджету України за 2002–2011 роки. Побудовано прогнозну модель бюджетного фінансування української освіти і науки. Визначено динаміку часток державних видатків на освіту і науку у доходах і видатках країни. Цим показникам дано назву статистичних хвиль бюджетного фінансування освіти і науки в Україні.
Статистичні хвилі бюджетного фінансування освіти і науки в Україні
Keywords: statistical waves; статистичні хвилі; dynamics; динаміка; prognosis model; прогнозна модель; education and science; освіта і наука; the State budget of Ukraine; Державний бюджет України; profits and charges; доходи і видатки